Baicalin promotes β-1,3-glucan exposure in Candida albicans and enhances macrophage response - Pan, Yiyuan; Shi, Zhaoling; Wang, Yadong; Chen, Feng; Yang, Yue; Ma, Kelong; Li, Wenqian (Frontiers in Cellular and Infection Microbiology, 2024)
Among the diverse fungal opportunistic pathogens, Candida albicans garners significant attention due to its wide range of infections and high frequency of occurrence. The emergence of resistance and the limited number of antifungals drives the need to develop novel antifungal drugs. Although the natural product baicalin has been shown to trigger apoptosis in C. albicans in previous experiments, its influence on cell wall (CW) structure along with immune recognition remains elusive. In this work, baicalin showed a significant killing effect against C. albicans SC5314. Moreover, CW destruction, characterized by β-1,3-glucan unmasking and chitin deposition, was observed as a consequence of the treatment with baicalin. The RNA sequencing analysis revealed that treatment with baicalin resulted in eight hundred forty-two differentially expressed genes (DEGs). Sixty-five genes, such as GSC1, ENG1, CHS3, GWT1, and MKC1, were associated with CW organization or biogenesis. Baicalin-pretreated C. albicans SC5314 was phagocytosed more efficiently by RAW264.7 macrophages, accompanied by increased TNF-α and IL-1β production. Accordingly, it is hypothesized that baicalin could stimulate β-1,3-glucan unmasking by governing CW-associated gene expression in C. albicans SC5314, which contributes to macrophage recognition and clearance.